Attitudinal professionalism under administrative embedding: evidence from social workers in urban China - Liu, Ziyu; Wong, Hung (Frontiers in Psychology, 2025)
IntroductionAttitudinal professionalism—comprising individual values, role orientations, and perceived discretion—is central to understanding social workers' professional behavior. In China, social work operates within an administratively embedded service regime shaped by government purchase-of-service contracts, raising questions about how organizational embedding and socialization processes influence professionals' value orientations and perceived autonomy. This study examines the multidimensional structure of attitudinal professionalism among urban social workers and the factors associated with its variation.MethodsAn online survey was administered to 667 frontline social workers in Guangzhou, Shenzhen, and Shanghai. Five attitudinal dimensions were measured: professional organization reference, public service, self-regulation, sense of calling, and perceived autonomy. Multiple regression analyses were conducted to estimate associations with professional socialization indicators (education, certification, tenure, gender) and organizational embedding, operationalized as organizational dependence on government purchase-of-service contracts.ResultsRespondents demonstrated strong commitments to public service and calling but lower levels of perceived autonomy, indicating a value-discretion divergence consistent with managerial and contractual service logics. Organizational independence—lower reliance on government contracts—was positively associated with value-oriented dimensions. In contrast, higher educational attainment and formal certification were negatively associated with certain professionalism dimensions, suggesting exam-centric training pathways and uneven practice-integrated socialization. Overall, occupational value orientations appeared relatively resilient despite reduced discretionary space.DiscussionThe findings reveal how administrative embedding shapes attitudinal professionalism in China's social service organizations. Methodologically, the study contributes a multidimensional operationalization of attitudinal professionalism; conceptually, it situates micro-level orientations within a layered framework spanning macro policy environments, meso organizational governance, and individual socialization. Implications for social work education, policy design, and organizational management are highlighted.